2008
DOI: 10.1016/j.jcrs.2008.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral endophthalmitis after bilateral sequential phacoemulsification

Abstract: An 81-year-old woman had uneventful bilateral sequential phacoemulsification using a separate sterile technique for each eye. Despite this, early culture-positive postoperative endophthalmitis developed. Management included bilateral intravitreal antibiotic agents, and the patient achieved an excellent visual outcome. To our knowledge, this is the third reported case of bilateral endophthalmitis after bilateral sequential phacoemulsification and the first reported case in which a separate sterile technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…Four cases of bilateral simultaneous endophthalmitis have been documented in the literature since 1952. [31][32][33][34][35] Arshinoff and Odorcic 4 reviewed and summarized these reports, noting that in all cases, a breach of sterile technique occurred. There have been no reported cases of bilateral simultaneous endophthalmitis after ISBCS when complete sterile separation of the 2 procedures was followed according to the "Suggestions for Safe ISBCS" on the iSBCS web site.…”
Section: Discussionmentioning
confidence: 99%
“…Four cases of bilateral simultaneous endophthalmitis have been documented in the literature since 1952. [31][32][33][34][35] Arshinoff and Odorcic 4 reviewed and summarized these reports, noting that in all cases, a breach of sterile technique occurred. There have been no reported cases of bilateral simultaneous endophthalmitis after ISBCS when complete sterile separation of the 2 procedures was followed according to the "Suggestions for Safe ISBCS" on the iSBCS web site.…”
Section: Discussionmentioning
confidence: 99%
“…4,18-20,24, 25 Arshinoff and colleagues 4 published the largest cohort of patients (1,020) undergoing SBIS, reporting that the common thread to all cases of bilateral endophthalmitis after SBIS is a lack of strict aseptic separation of the 2 surgeries. 2, 28 Arshinoff and the American Academy of Ophthalmology 2,17 also reported that of approximately 33,000 cases of simultaneous bilateral cataract surgery performed by 6 surgeons, 10 cases resulted in unilateral endophthalmitis and none in bilateral endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] SBIS has been performed in tens of thousands of adult patients, 2,17 with rare reports of bilateral complications. 4,[18][19][20][21][22][23][24][25] There are few reports of SBIS in children in the literature, with a total of 163 cases of bilateral cataract surgeries in children up to 19 years of age and a similar number of cases of bilateral congenital glaucoma surgery (either goniotomy or primary combined trabeculotomy/trabeculectomy). [9][10][11][12][13][14][15][16]26 Only one paper 12 reports pediatric bilateral simultaneous cataract surgery performed in North America-a study of 16 patients, most of whom had systemic abnormalities that may have increased their anesthetic risk.…”
mentioning
confidence: 99%
“…6 Published series of same-day bilateral cataract surgery have yet to report a single case of bilateral endophthalmitis; however, for rare events one needs large numbers of patients to generate sufficient power. 12 There have been four cases of bilateral endophthalmitis following ISCS reported in the literature, [13][14][15] including one from the UK; however, in each of these cases stricter sterile separation of the two eyes may have prevented the complication. 16 Outbreaks of endophthalmitis have been attributed to factors including contaminated intraocular lenses, saline, phacoemulsifiers, and intraocular irrigation solutions.…”
mentioning
confidence: 99%